Human virome: Implications in cancer - Rafael Tamayo-Trujillo; Patricia Guevara-Ramírez; Santiago Cadena-Ullauri; Elius Paz-Cruz; Viviana A. Ruiz-Pozo; Ana Karina Zambrano (Heliyon, 2023)
In recent years, the human virome has gained importance, especially after the SARS-CoV-2 pandemic, due to its possible involvement in autoimmune, inflammatory diseases, and cancer. Characterization of the human virome can be carried out by shotgun next-generation sequencing (metagenomics), which allows the identification of all viral communities in an environmental sample and the discovery of new viral families not previously described. Variations in viral quantity and diversity have been associated with disease development, mainly due to their effect on gut bacterial microbiota. Phages can regulate bacterial flora through lysogeny; this is associated with increased susceptibility to infections, chronic inflammation, or cancer. The virome characterization in different human body ecological niches could help elucidate these particles' role in disease. Hence, it is important to understand the virome's influence on human health and disease. The present review highlights the significance of the human virome and how it is associated with disease, focusing on virome composition, characterization, and its association with cancer.